The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.fuel.2012.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Optimum temperature for sulphur retention in fluidised beds working under oxy-fuel combustion conditions

Abstract: Oxy-fuel combustion is one of the leading options for power generation with CO 2 capture. The process consists of burning the fuel with a mixture of nearly pure oxygen and a CO 2 -rich recycled flue gas, resulting in a product flue gas from the boiler containing mainly CO 2 and H 2 O. Among the possible boiler types, fluidised bed combustors are very appropriate for the oxy-fuel process because they allow the in-situ desulphurisation by feeding Ca-based sorbents into the combustor.In this work, the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 25 publications
2
53
1
1
Order By: Relevance
“…The possible reasons had been proposed by many authors and these were summarized by Tarelho et al [8] into two main explanations: (i) the temperature effect on the physical properties of the limestone and (ii) the reductive decomposition of CaSO 4 at higher temperatures. The increase of SO 2 concentration always enhances the sulfation rate of the CaO, as shown in the research of Abanades et al [23] and Diego et al [11]. Smaller sorbent particle size is favorable for the reaction of CaO and SO 2 because of the larger specific surface area smaller particles has [10,24].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The possible reasons had been proposed by many authors and these were summarized by Tarelho et al [8] into two main explanations: (i) the temperature effect on the physical properties of the limestone and (ii) the reductive decomposition of CaSO 4 at higher temperatures. The increase of SO 2 concentration always enhances the sulfation rate of the CaO, as shown in the research of Abanades et al [23] and Diego et al [11]. Smaller sorbent particle size is favorable for the reaction of CaO and SO 2 because of the larger specific surface area smaller particles has [10,24].…”
Section: Introductionmentioning
confidence: 80%
“…CFBB can be used to combust many types of fuels including different kinds of coals, coke, and biomass [1][2][3][4][5][6][7]. Apart from its excellent fuel flexibility, other advantages of CFBB are the low NOx production due to its low combustion temperature, and low SO 2 emissions which are attributed to the in situ desulfurization using calcium based sorbents [8][9][10][11]. Limestone as an economical desulfurization sorbent has been investigated intensively in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…10 A possible reason for this phenomenon in the present study is that all of the tests were conducted with furnace temperatures around 850°C, which is not the optimum temperature for sulfur capture. A report by de Diego et al 17 describing tests conducted using a small-scale bubbling fluidized-bed (BFB) rig has shown that, under oxy-fuel combustion conditions, the optimum temperature to achieve the highest sulfur retention was 900−925°C, whereas operations using enriched air required optimum combustion temperatures of 850−870°C. The IET/CAS facility continues to conduct research in the field of high-concentration oxy-fuel CFB technology.…”
Section: Resultsmentioning
confidence: 99%
“…The coal participates by 60% in SO 2 emissions, the crude oil participates by 30% and the rest 10% of SO 2 emissions is due to the combustion of pyrites and mineral sulfur. The limestone and the lime have been used for SO 2 capture in fluidized bed or pulverized coal combustors . The use, still, of fluidized bed technology in Greece and other countries is prohibitive due to the very high replacement cost of existing combustors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various technologies for flue gas desulfurization (FGD) can be classified into three different types: wet scrubbers, semi‐dry processes and dry processes. Wet scrubbers have been widely commercialized in industry for achieving SO 2 removal in excess of 95% . However, this kind of technology generates a large amount of wet solid waste and requires treatment of waste water.…”
Section: Introductionmentioning
confidence: 99%